Early Warning System: Solusi Klaim Negatif Rumah Sakit Program Jaminan Kesehatan Nasional - Yuki Firmanto (Jurnal Ekonomi Akuntansi dan Manajemen, 2021)
Hospital bills that are greater than the INA CBGs rate results in losses being charged to the hospital so that it hinders thefulfillment of hospital operational needs. The purpose of this study was to provide an overview of the SIMRS development process by implementing the concept of an early warning system in mitigating BPJS negative claims experienced by RSUD X. The study was conducted at the X Regional General Hospital (RSUD) in Probolinggo. The case study approach was adopted using the data analysis model Framework for the application of systems thinking (FAST). Analysis of the data obtained shows that the existence of BPJS claim information for each patient that can be known in real-time will help mitigate negative claims so as to reduce the risk of loss to the hospital. Referring to this, the resulting output in the form of an early warning system concept was developed using a direct warning model to users with the output of patient billing information. This development can support hospital operations to be effective and efficient. Keywords: BPJS claims, Early Warning System, Framework for the Application of System Thinking